Cardiac Arrhythmias in Patients with Electrical Injury: Hospital Based Study - Dhital, Bishnu Mani; Regmi, Sudhir; Regmi, Shyam Raj; Shrestha, Bidhan; Budhathoki, Keshav; GC, Ananda; Sedhai, Sabina; Khan, Amir; Murtuza, Shahid; Gurung, Puran; et al. (Nepalese Heart Journal, 2020)
Background: Electrical injury and its consequences after exposure to electric shock has been associated with an increased risk of developing immediate and delayed cardiac arrhythmias. The aim of this study was to evaluate the prevalence of cardiac arrhythmias and different symptoms in patient with high voltage and low voltage electrical injury. Methods: All 50 consecutive patients who were admitted in Chitwan Medical College from April 2018 to March 2020 were prospectively studied. Patients were categorized into high and low voltage injury group and their variables were compared. Results: The mean age of the patients was 32.3±10.4 years among them 41 (82%) were male. Patients who sustain high voltage electrical injury (>1000V) were 18 (36%) and low voltage injury (<1000V) were 32 (64%). Cardiac arrhythmias like sinus tachycardia (11.1% vs 6.2%, p=0.054), sinus bradycardia (11.1% vs 3.1% p=0.254), ventricular premature beats (5.6% vs3.1%, p=0.674), atrial fibrillation (11.1% vs 0%, p=0.054) were observed in high voltage and low voltage group. The commonest presenting symptoms in both groups were pain (77.8% vs 84.4% p=0.560) and fatigue (55.6% vs 40.6%, p=0.328). Conclusion: In this study few non fatal cardiac arrhythmias were observed in both high and low voltage electrical injury group. There is no significant difference in the presenting symptoms and types of arrhythmias observed between low voltage and high voltage injury group.